2019
DOI: 10.1111/codi.14866
|View full text |Cite
|
Sign up to set email alerts
|

Renal impairment after ileostomy formation: a frequent event with long‐term consequences

Abstract: Aim High stoma output and dehydration is common following ileostomy formation. However, the impact of this on renal function, both in the short term and after ileostomy reversal, remains poorly defined. We aimed to assess the independent impact on kidney function of an ileostomy after rectal cancer surgery and subsequent reversibility after ileostomy closure. Methods This retrospective single‐site cohort study identified patients undergoing rectal cancer resection from 2003 to 2017, with or without a diverting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 55 publications
3
71
0
Order By: Relevance
“…The long‐term impact of a temporary ileostomy should not be underestimated. A recent study showed that ileostomy formation is independently associated with kidney injury and that this persists with long‐term follow‐up 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…The long‐term impact of a temporary ileostomy should not be underestimated. A recent study showed that ileostomy formation is independently associated with kidney injury and that this persists with long‐term follow‐up 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…Dehydration has been cited as the most common reason for re‐admission accounting for 40–62% of all re‐admissions 6,7 . Short‐term renal impairment following ileostomy formation is shown to impart long‐term consequences, with patients suffering higher risk of moderate to severe chronic kidney disease up to 1 year after the index operation 8 . Dehydration‐related re‐admissions are expensive, estimated at US$2750 and US$9107 per re‐admission for dehydration and renal failure, respectively 9 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, given the possible complications associated with the presence of ileostomy, such as electrolyte disturbances, renal dysfunction, and the risk of surgical complications associated with the ileostomy itself and ileostomy closure procedures, it is necessary to define the group of patients who actually benefit from elective diversion [ 4 6 ]. The rate of non-closure of the stoma is difficult to compare due to different criteria adopted by authors, including different latest expected time to closure which ranges from 9 to 36 months.…”
Section: Introductionmentioning
confidence: 99%